2011
DOI: 10.3389/fnmol.2011.00010
|View full text |Cite
|
Sign up to set email alerts
|

Antisense-Mediated RNA Targeting: Versatile and Expedient Genetic Manipulation in the Brain

Abstract: A limiting factor in brain research still is the difficulty to evaluate in vivo the role of the increasing number of proteins implicated in neuronal processes. We discuss here the potential of antisense-mediated RNA targeting approaches. We mainly focus on those that manipulate splicing (exon skipping and exon inclusion), but will also briefly discuss mRNA targeting. Classic knockdown of expression by mRNA targeting is only one possible application of antisense oligonucleotides (AON) in the control of gene fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 119 publications
(158 reference statements)
0
20
0
Order By: Relevance
“…Given that the BBB is also a dynamic regulatory interface for bidirectional peptide transport [2,3], there is much interest in utilizing these transport systems for drug delivery to the brain. Previously, our lab and others have used phosphorothioated antisense oligonucleotides to modify protein expression in vivo [4][5][6][7]. We have also demonstrated that these antisense oligonucleotides have a saturable BBB transport system which allows them to access the CNS and alter expression of their protein targets [5,8,9].…”
Section: Introductionmentioning
confidence: 83%
“…Given that the BBB is also a dynamic regulatory interface for bidirectional peptide transport [2,3], there is much interest in utilizing these transport systems for drug delivery to the brain. Previously, our lab and others have used phosphorothioated antisense oligonucleotides to modify protein expression in vivo [4][5][6][7]. We have also demonstrated that these antisense oligonucleotides have a saturable BBB transport system which allows them to access the CNS and alter expression of their protein targets [5,8,9].…”
Section: Introductionmentioning
confidence: 83%
“…Moreover, AONs are small molecules that easily penetrate into tissues and are taken up by neurons without complex chemical formulations or packaging vehicles. 30 For its application to treat optic atrophy and thus targeting retinal ganglion cells an administration through intravitreal injection can be envisaged. Another advantage of AON over classical gene therapy approaches is the possibility to discontinue treatment at any time, in case of side-effects which may occur.…”
Section: Discussionmentioning
confidence: 99%
“…With exon skipping, AONs are used that target-specific splicing signals, masking an exon in the pre-mRNA from the splicing machinery and thus resulting in exclusion of the target exon from the mRNA [208, 209]. When the correct reading frame is maintained, subsequent translation will result in formation of an internally truncated protein.…”
Section: Preventing Formation Mutant Ataxin-3mentioning
confidence: 99%